Enhancing BWC Implementation in Moldova - Lampalzer, Hermann Alex (One Health & Risk Management, 2025)
The Biological Weapons Convention (BWC) celebrates its 50th anniversary this year. Building on the foundations of the 1925 Geneva Protocol, the Convention has established a strong and comprehensive norm against an entire category of Weapons of Mass Destruction.Recognizing the evolving risks posed by rapid scientific advancements and the dualuse nature of life sciences, the Republic of Moldova, a State Party to the Convention since 2005, recently appointed its National Agency for Public Health as its BWC National Contact Point to strengthen national implementation and collaboration.The BWC Implementation Support Unit looks forward to working closely with the National Agency for Public Health in the Republic of Moldova to further strengthen the national implementation of the Convention and congratulates the Moldavian Biosafety and Biosecurity Association on its publication “One Health & Risk Management” in support of these efforts.